2018
DOI: 10.1017/s0001972018000517
|View full text |Cite
|
Sign up to set email alerts
|

Resource politics and the impact of Chinese involvement in small-scale mining in Ghana

Abstract: Luning and Pijpers (2017) give a valuable analysis of the interplay between politics and geology in forms of cohabitation between international mining companies and small-scale mining operators on large-scale concessions, which reveals much about the ways in which existing power relations are challenged. 'Indepth geopolitics', inclusive of the three-dimensional perspective, is an innovative concept that highlights important components of the dynamics at work from the state to the community level, and shows how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…And if not for the growing illegality and massive environmental destructions associated with the operations, ASM is the exclusive right of the natives ( Akabzaa and Darimani, 2001 ; Ofosu-Mensah, 2010 ). Additionally, the position of migrants in the galamsey sector has been highlighted ( Nyame et al., 2009 ; Hilson et al., 2014 ; Antwi-Boateng and Akudugu, 2020 ), but fortunately for the Upper West Region, the devastating environmental effect of the illegal Chinese migrants including worsening social consequences in local mining communities as reported by a large body of the literature ( Hilson et al., 2014 ; Hilson, 2017 ; Botchwey and Crawford, 2018 ; Antwi-Boateng and Akudugu, 2020 ; Hausermann et al., 2020 ) were dim in this study.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…And if not for the growing illegality and massive environmental destructions associated with the operations, ASM is the exclusive right of the natives ( Akabzaa and Darimani, 2001 ; Ofosu-Mensah, 2010 ). Additionally, the position of migrants in the galamsey sector has been highlighted ( Nyame et al., 2009 ; Hilson et al., 2014 ; Antwi-Boateng and Akudugu, 2020 ), but fortunately for the Upper West Region, the devastating environmental effect of the illegal Chinese migrants including worsening social consequences in local mining communities as reported by a large body of the literature ( Hilson et al., 2014 ; Hilson, 2017 ; Botchwey and Crawford, 2018 ; Antwi-Boateng and Akudugu, 2020 ; Hausermann et al., 2020 ) were dim in this study.…”
Section: Resultsmentioning
confidence: 82%
“…It indicated that small-scale mining is exclusively preserved for citizens. Moreover, the high cost of acquiring the small-scale mining license, bureaucracy, corruption, collusion and collaboration as well as massive political interference have been highlighted as drawbacks to the majority of the local miners' inability to acquire the small-scale mining license (Kwai and Hilson, 2010;Botchwey and Crawford, 2018;Adu-Baffour et al, 2021;Gbedzi et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…This has led to illegal small-scale gold mining locally referred to as ‘Galamsey’. While once conducted at a relatively small scale using manual methods, according to the literature on the topic, the rise in global gold prices starting in 2008 and new industrial-scale mining technology brought into the country by Chinese miners (beginning in 2009 and peaking in 2013) exacerbated the problem and international political and economic pressure and corruption stymied regulation [ 36 ]. Illegal mining has led to deforestation and the destruction of agricultural land since it is more profitable than traditional farming.…”
Section: Resultsmentioning
confidence: 99%
“…The negative effect of ASM on land is clear: It removes topsoil and creates pits and, where remediation is inadequate, renders mining areas unsuitable for other uses. The effect of ASM on water bodies has been highly publicised, including the total shutdown of some water treatment plants (the plants were unable to cope with the poor quality intake) and a reported reduction of 50% of the volume of water available for treatment by the Ghana Water Company (Botchwey, 2018). The belief that ASM has minimal effect on forests could conceivably be due to legal SSMs not being allowed to operate in forest zones, and therefore, they believed that damage was only caused by galamsey .…”
Section: Asm In Ghanamentioning
confidence: 99%